Palmitoylation-regulated interactions of the pseudokinase calmodulin kinase-like vesicle-associated with membranes and Arc/Arg3.1 - Barylko, Barbara; Hedde, Per Niklas; Taylor, Clinton A.; Binns, Derk D.; Huang, Yu-Kai; Molinaro, Gemma; Huber, Kimberly M.; Jameson, David M.; Albanesi, Joseph P. (Frontiers in Synaptic Neuroscience, 2022)
CaMKv, a pseudokinase belonging to the Ca2+/calmodulin-dependent kinase family, is expressed predominantly in brain and neural tissue. It may function in synaptic strengthening during spatial learning by promoting the stabilization and enrichment of dendritic spines. At present, almost nothing is known regarding CaMKv structure and regulation. In this study we confirm prior proteomic analyses demonstrating that CaMKv is palmitoylated on Cys5. Wild-type CaMKv is enriched on the plasma membrane, but this enrichment is lost upon mutation of Cys5 to Ser. We further show that CaMKv interacts with another regulator of synaptic plasticity, Arc/Arg3.1, and that the interaction between these two proteins is weakened by mutation of the palmitoylated cysteine in CamKv.